Somebody to love : the life, death and legacy of Freddie Mercury - Richards, Matt, 1967-; Langthorne, Mark (Weldon Owen, 2016)
In Somebody to Love, biographers Mark Langthorne and Matt Richards skilfully [sic] weave together Freddie Mercury's incredible pursuit of musical greatness with Queen, his upbringing and his endless search for love with the story of a terrible disease that swept across the world in the 1980s, as medical treatment fought to catch up with it despite underfunding, social ignorance, and homophobia. With brand-new perspectives from Mercury's closest friends and fellow musicians, this unique and deeply moving tribute casts a very different light on both his death and the origins of AIDS itself. An intimate read, this book--like Freddie and his art--will stay with you for a long time to come." [jacket flyleaf].